Arterial vascularization of the mammary gland in goats (Capra hircus, Linnaeus, 1758) - Rosemberg, Luiz Carlos; Miglino, Maria Angelica (Brazilian Journal of Veterinary Research and Animal Science, 2000)
We studied the distribution and vascular disposition of arteries in the mammary gland of 30 adult, mixed-breed goats, which came from the states of Ceará and Minas Gerais. In order to perform this study we analyzed schematic drawings taken from models, which were obtained through "latex neoprene 450" injection, followed by fixation in 10% aqueous solution and dissection. We noticed that the blood supply for each half of the mammary gland is carried out by the external pudendal artery and is complemented by connections to branches of the internal pudendal artery and internal thoracic artery. Close to the mammary gland the external pudendal artery bends and sends out the superficial mammary branch. After that it is called A. mammaria until its bifurcation; it also sends out branches to mammary lymph nodes and ventral labium. When it penetrates the gland the cranial mammary artery divides itself, thus forming the cranial and medial mammary arteries, which send several branches throughout the mammary gland and to the skin that covers this region. The cranial mammary artery leaves the mammary gland and runs cranially along the ventral abdominal wall until it reaches the navel, yet as superficial caudal epigastric artery. We did not identify significant differences between the vascular disposition in both sides of the mammary gland. We reported the occurrence of anastomoses between the medial mammary arteries and their branches, and also took note of the type, site and frequency these occurred. Our work was concluded with a comparative analysis confronting it to research of other authors, who studied the blood supply of the mammary gland in cattle.